Effects of Climate Changes on the Pasture Productivity From 1961 to 2016 in Sichuan Yellow River Source, Qinghai-Tibet Plateau, China - Zhang, Lv; Xiao, Pengfei; Yu, Hui; Zhao, Tao; Liu, SiYuan; Yang, Li; He, Yu; Luo, Yong; Wang, Xiao; Dong, Wei; He, Hui; Wang, Duyang; et al. (Frontiers in Ecology and Evolution, 2022)
Meteorological station data from 1961 to 2016 in the Sichuan Yellow River Source (SYRS) was used to analyse the trends in precipitation and temperature. The Thornthwaite Memorial model and GIS technology were used to calculate the response of pasture productivity to climate change. A climate prediction model of pasture productivity was established to predict its response to precipitation and temperature. The results showed that: (1) the annual precipitation presents a slight downward trend, at a rate of -10.16 mm·(10a)-1. The average annual temperature exhibited an upward trend, at (10a)-1, and the productivity of herbage exhibited a linearly increasing trend, with a rate of increase of 80.07 g·m-2·(10a)-1. (2) In terms of spatial distribution, the pasture productivity decreased from southwest to northeast. The influence of temperature on pasture productivity was greater than that of precipitation in the SYRS. (3) The ‘warm - wet’ climate was conducive to increasing pasture productivity. The annual average temperature was predicted to increase by 1℃ or 2℃, and the annual average precipitation was predicted to increase by 10% or 20% with an average increase between 7.15% and 14.30%. (4) Grassland degradation continues to occur and ecological restoration measures should be implemented to control grassland degradation.